Structure change and urban inequality in the People's Republic of China - Yuan Zhang; Guanghua Wan (Asian Development Bank Institute (ADBI), 2017)
The People's Republic of China (PRC) is thought to be one of the most unequal economies in the world, but very few studies ever touched on the determinants and the evolution of its urban inequality. This paper firstly applies the inequality decomposition method to an urban household sample covering the period from 2003-2012, and finds that wage inequality of urban households is dominated by inequality component within service industry, and also its decline after 2008 is mainly attributable to the declining inequality component within the service industry. Secondly, we provide evidence indicating that the change in employment structure and wage determination in the urban labor market can help reduce wage income inequality in urban PRC. These results can help explain the fact that inequality in urban PRC no longer shows deterioration after 2008. Policy implications are also proposed at the end of this paper.
Keywords: D63; P25; 330; Economics; Industry and trade; China; People's Republic of